2020
DOI: 10.1096/fj.202001020r
|View full text |Cite
|
Sign up to set email alerts
|

The ACE2‐deficient mouse: A model for a cytokine storm‐driven inflammation

Abstract: Angiotensin converting enzyme 2 (ACE2) plays an important role in inflammation, which is attributable at least, in part, to the conversion of the pro-inflammatory angiotensin (Ang) II peptide into angiotensin 1-7 (Ang 1-7), a peptide which opposes the actions of AngII. ACE2 and AngII are present in many tissues but information on the cornea is lacking. We observed that mice deficient in the Ace2 gene (Ace2 −/−), developed a cloudy cornea phenotype as they aged. Haze occupied the central cornea, accompanied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 55 publications
4
44
0
Order By: Relevance
“…Activation of the S protein is important for the entry of the virus into cells by fusion of the viral outer membrane with the cell membrane. Furthermore, ACE2 deficiency, which could be induced by binding with SARS-CoV-2, is considered to drive a cytokine storm in patients with COVID-19 [ 19 ].…”
Section: Spike Domain In Coronavirusmentioning
confidence: 99%
“…Activation of the S protein is important for the entry of the virus into cells by fusion of the viral outer membrane with the cell membrane. Furthermore, ACE2 deficiency, which could be induced by binding with SARS-CoV-2, is considered to drive a cytokine storm in patients with COVID-19 [ 19 ].…”
Section: Spike Domain In Coronavirusmentioning
confidence: 99%
“…Control NP treated corneas displayed a range of thickened and disorganized corneal epithelia as well as a wide spectrum of stromal alterations, ranging from a stroma filled with inflammatory cells (Figure 6C) to randomly oriented collagen bundles resulting in a disorganized appearance (Figure 6D). The infiltrates were identified as T cells by immunohistochemical (IHC) staining [ 53 ] for CD3 at day 7 (Figure S9, Supporting Information). In contrast, the HDL NP‐treated corneas showed well‐organized stratified epithelia (Figure 6E,F) and stroma with collagen bundles highly organized in a plywood‐like fashion that were relatively devoid of inflammatory cells (Figure 6E,F and Figure S8, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Downregulation of ACE2 during the entry of the virus into the host cells leads to an increase in angiotensin II/angiotensin(1-7) ratio with proinflammatory, pro-apoptotic, destructive and pro-thrombotic effects [27, 46]. In animal studies, it was shown that ACE2 deficiency in mice and infusion of Ang II in swine resulted in corneal inflammatory response and lung pathology, respectively, resembling exactly the immunopathological changes seen in COVID-19 [47, 48]. In an in-silico study, Losartan was shown to change the tertiary structure of ACE2 in binding with receptor binding domain (RBD) of S protein of the virus as well as inducing modification in conformational shape of SARS-CoV-2 papain-like protease [27].…”
Section: Discussionmentioning
confidence: 99%